2007
DOI: 10.1086/523278
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Perceptions, Beliefs, Attitudes, and Knowledge Concerning Antimicrobial Resistance in a Brazilian Teaching Hospital

Abstract: This cross-sectional survey assessed physicians' perceptions, knowledge and practices concerning antimicrobial resistance. Ninety-nine percent of participants reported that they perceived antimicrobial resistance as an important problem, and 86.7% agreed that antimicrobials are overprescribed, but only 2.9% rated "practicing antimicrobial control" as the most important strategy for preventing resistance. The results of this study warrant educational programs on antimicrobial resistance and the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
42
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 8 publications
14
42
2
Order By: Relevance
“…26,27 Previous studies have found that respondents underestimated the prevalence of resistance, particularly at their own institution. 21,24,25 As noted in previous studies and our study, most healthcare providers believed that excess use of antimicrobials was a cause of resistance, 24,25 but fewer believed that antimicrobials were overused in the hospitals in which they worked. 22,23 Our survey uncovered a substantial knowledge gap which may delay appropriate implementation of transmission precautions and thus facilitate transmission of multidrugresistant organisms.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…26,27 Previous studies have found that respondents underestimated the prevalence of resistance, particularly at their own institution. 21,24,25 As noted in previous studies and our study, most healthcare providers believed that excess use of antimicrobials was a cause of resistance, 24,25 but fewer believed that antimicrobials were overused in the hospitals in which they worked. 22,23 Our survey uncovered a substantial knowledge gap which may delay appropriate implementation of transmission precautions and thus facilitate transmission of multidrugresistant organisms.…”
Section: Discussionsupporting
confidence: 51%
“…20 Several surveys about antimicrobial resistance have been conducted with different types of healthcare workers, including medical students, residents, and attending physicians (Table 6). [21][22][23][24][25] These previous studies have found that 87% to 97% of respondents viewed resistance as a national problem while fewer (55% to 93%) viewed resistance as a local problem. 17,19,[21][22][23][24] In contrast, we found that the vast majority of respondents at our institution agreed that MDR-GNB infections were a serious problem in ICUs both in the U.S. and at our medical center.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KAP-surveys about antimicrobial resistance have been conducted among doctors in the community setting, but only few have been reported from the hospital setting. 6,7 The bacterial disease burden in India is very high. So antibiotics play a huge role in controlling morbidity and mortality from such diseases.…”
Section: Introductionmentioning
confidence: 99%